Self‐administered biofeedback treatment app for pediatric migraine: A randomized pilot study. Issue 2 (8th December 2020) - Stubberud, Anker; Linde, Mattias; Brenner, Eiliv; Heier, Martin; Olsen, Alexander; Aamodt, Anne Hege; Gravdahl, Gøril B.; Tronvik, Erling
Abstract: Objective: To investigate the effect size, safety, and tolerability of a therapist‐independent biofeedback treatment app among adolescent with migraine. Materials and Methods: This was a prospective, 3:1 ratio randomized, sham‐controlled, double‐blind, pilot study with 16 adolescents diagnosed with migraine randomized to eight weeks of biofeedback treatment ( n = 12) or sham biofeedback ( n = 4), carried out at two university hospitals in Norway. The prespecified and primary objective of the study was to observe changes in outcomes within the active treatment group. The sham control group was included in a minor ratio primarily to evaluate its feasibility. The primary outcome was change in headache frequency. A modified intention to treat analysis was performed, including participants completing at least seven biofeedback sessions in weeks 1–4 ( n = 12 vs. n = 4) and weeks 5–8 ( n = 7 vs. n = 2). Results: Adherence was poor with 40% (136/336) of planned biofeedback sessions completed during weeks 5–8. Within the biofeedback group, a not statistically significant reduction in headache frequency was observed at weeks 1–4 (2.92 days/month, 95% CI −1.00 to 6.84, p = .145) and weeks 5–8 (1.85 days/month, 95% CI −2.01 to 5.72, p = .395). The biofeedback group experienced a median of one fewer headache days/month versus sham that did not reach significance (95% CI −4.0 to 9.0, p = .760). Conclusions: We observed a small reduction in headache frequency in the active treatment group. Findings were likely undermined by low adherence and underpowered analyses but indicate that a therapist‐independent biofeedback treatment app has the potential to be an effective, tolerable, and inexpensive treatment option. Abstract : Biofeedback is an effective migraine treatment; however, a completely therapist‐independent smartphone administered treatment for children and adolescents has not been investigated. In this randomized controlled trial, we show that smartphone biofeedback treatment has the potential to be an effective in pediatric migraine, reducing migraine frequency by approximately 30%.